Pengaruh Kemampuan Sumber Daya Manusia, Kualitas Audit, dan Ketaatan Aturan Akuntansi terhadap Ketepatan Waktu Penyampaian Laporan Keuangan Enititas Studi pada Badan Standarisasi Nasional (BSN) - Basri, Husen; Iskak, Jamaludin (Jurnal Manajemen Bisnis dan Keuangan, 2023)
This study aims to obtain empirical evidence of the influence of human resource capabilities, audit quality, and adherence to accounting rules on the timeliness of submission of entity financial reports (study at the National Standardization Agency). The population in this study are employees who work in the finance section of the National Standardization Agency. Sampling was carried out using accidental sampling. The primary data collection method used is the questionnaire method. Data were analyzed using multiple linear regression. The results showed that human resources had a positive effect on the timeliness of submission of entity financial reports, audit quality had a positive and significant effect on the timeliness of submission of entity financial reports, compliance with the rule of law had a positive and significant effect on the timeliness of submission of entity financial reports.